RETRACTED: Novel Insights Into the Role of Mitochondria-Derived Peptides in Myocardial Infarction - Wu, Dan; Kampmann, Enny; Qian, Geng (Frontiers in Physiology, 2021)
Mitochondria-derived peptides (MDPs) are a new class of bioactive peptides encoded by small open reading frames (sORFs) within known mitochondrial DNA (mtDNA) genes. MDPs may affect the expression of nuclear genes and play cytoprotective roles against chronic and age-related diseases by maintaining mitochondrial function and cell viability in the face of metabolic stress and cytotoxic insults. In this review, we summarize clinical and experimental findings indicating that MDPs act as local and systemic regulators of glucose homeostasis, immune and inflammatory responses, mitochondrial function, and adaptive stress responses, and focus on evidence supporting the protective effects of MDPs against myocardial infarction. These insights into MDPs actions suggest their potential in the treatment of cardiovascular diseases and should encourage further research in this field.